Pigmented Tumour of the Eyelid with Unexpected Findings - Anne C. Hunold; Martina C. Herwig; Frank G. Holz; Hans-Peter Fischer; Karin U. Loeffler (Hindawi Limited, 2012)
A 63-year-old patient presented with a small painless nodular tumour of his left lower eyelid which had increased in size over the last few weeks. The tumour was excised by wedge resection and submitted for ophthalmopathologic examination. Histopathologic examination revealed a cystic lesion of apocrine origin with focal proliferations. The proliferative cells appeared pleomorphic and displayed marked atypia. Staining with Ki67 revealed a significant mitotic activity supporting the diagnosis of an apocrine adenocarcinoma of Moll. As the lesion displayed in most parts characteristics of a benign apocrine hidrocystoma, a thorough and critical histopathological examination is required in such cases to avoid missing an early malignant transformation.